2022
DOI: 10.1093/genetics/iyac033
|View full text |Cite
|
Sign up to set email alerts
|

Dual roles for nuclear RNAi Argonautes in Caenorhabditis elegans dosage compensation

Abstract: Dosage compensation involves chromosome-wide gene regulatory mechanisms which impact higher order chromatin structure and are crucial for organismal health. Using a genetic approach, we identified Argonaute genes which promote dosage compensation in C. elegans. Dosage compensation in C. elegans hermaphrodites is initiated by the silencing of xol-1 and subsequent activation of the Dosage Compensation Complex (DCC) which binds to both hermaphrodite X chromosomes and reduces transcriptional output by two-fold. A … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Tethering of heterochromatin is not unique to dosage compensation in C. elegans [121,122,180], but in conjunction with the DCC, it has a unique impact on the compaction and subnuclear localization of the X chromosomes. It has also been demonstrated that the nuclear RNAi machinery is also involved in X chromosome compaction and repression, but whether this effect is direct or indirect is not yet known [181]. A similar pathway involving Argonautes to establish heterochromatin has been observed in D. melanogaster [182].…”
Section: Elegans Dosage Compensation As a Paradigm For Chromosome-wid...mentioning
confidence: 92%
“…Tethering of heterochromatin is not unique to dosage compensation in C. elegans [121,122,180], but in conjunction with the DCC, it has a unique impact on the compaction and subnuclear localization of the X chromosomes. It has also been demonstrated that the nuclear RNAi machinery is also involved in X chromosome compaction and repression, but whether this effect is direct or indirect is not yet known [181]. A similar pathway involving Argonautes to establish heterochromatin has been observed in D. melanogaster [182].…”
Section: Elegans Dosage Compensation As a Paradigm For Chromosome-wid...mentioning
confidence: 92%
“…The DCC binds to recruitment sites on the X chromosome and spreads along the length of the chromosome to repress transcription [20], [21], [22], [23]. The DCC and the additional ancillary pathways it recruits use multiple mechanisms to establish and maintain dosage compensation on the hermaphrodite X chromosomes throughout somatic tissues in larvae and adults [24], [25], [26], [27], [28]. These include X-specific deposition of H4K20me1 repressive mark by DPY-21 [27], [28], [29], [30], tethering of H3K9me2/me3 regions to the nuclear lamina [25], contributions by the nuclear RNAi machinery [24], and the formation of TADs on the X chromosomes [26], [31].…”
Section: Introductionmentioning
confidence: 99%
“…The DCC and the addi,onal ancillary pathways it recruits use mul,ple mechanisms to establish and maintain dosage compensa,on on the hermaphrodite X chromosomes throughout soma,c ,ssues in larvae and adults [24], [25], [26], [27], [28]. These include X-specific deposi,on of H4K20me1 repressive mark by DPY-21 [27], [28], [29], [30], tethering of H3K9me2/me3 regions to the nuclear lamina [25], contribu,ons by the nuclear RNAi machinery [24], and the forma,on of TADs on the X chromosomes [26], [31]. The ini,a,on of dosage compensa,on in developing hermaphrodite embryos is linked to a loss in developmental plas,city and the onset of cellular differen,a,on programs [32], [33].…”
mentioning
confidence: 99%